On participation of anesthesiologists-resuscitators in the forensic medical examination - E. S. Netesin; V. I. Gorbachev (Вестник анестезиологии и реаниматологии, 2020)
The article describes certain key issues of participation of anesthesiologists and resuscitators as experts in criminal cases. The main documents that should guide the anesthesiologist-resuscitator during the examination are presented. Some expert conclusions are critically assessed demonstrating major flaws and invalidity of the made conclusions. Certain wishes and suggestions for the qualitative improvement of forensic examination are expressed.